PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 138 PEKANBARU - ', Yasril; ', Zulkifli; ', Hamizi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research aims to increase the student’s IPA outcomes at 5th grade in elementary school 138 Pekanbaru even semester the school year 2014/2015 in the subject matter of natural events by using cooperative learning model type jigsaw. Problems that affect student learning outcomes are a) Most of the students passive in the learning process, b) Lack of enthusiasm the students in the learning because teacher always use lecture method, c) Smart student don’t want to help students weak in the learning process, especially in group discussion activities. The subject in this research are 5th grade student’s elementary school 138 Pekanbaru that totally is 30 who is 12 male students and 18 female students. Object in the research is to increase the student’s IPA outcomes by using cooperative learning model type jigsaw at 5th grade in elementary school 138 Pekanbaru. This research is two cycles, the each cycle consisting of two meetings and test. The average percentage of the students before using the model is 40%, is increased 60% in the first cycle and increase 86.7% in the second cycle. The average student’s learning outcomes increase from base score to first cycle is 8.2% , the second cycle average student’s learning outcomes is 20.2%. Basically the student’s learning outcomes can be show of cooperative learning model type jigsaw can to increase the student’s IPA outcomes at 5th grade in elementary school 138 Pekanbaru.Keywords: Cooperative Learning Model Type Jigsaw, IPA learning outcomes